Successful pregnancy of a Maine Coon queen despite feline mammary fibroadenomatous hyperplasia recurrence after treatment with aglepristone - P Socha; P Mossakowski (Veterinární Medicína)
One of the disorders of the mammary gland in the queen is feline mammary fibroadenomatous hyperplasia (FMFH), caused by an increasing concentration of progesterone (P4) and some other local growth factors. It occurs mostly during puberty after the heat characterised by spontaneous or provoked ovulation, as a result of exogenous progesterone intake and sometimes during pregnancy. To diagnose a 14-month-old intact Maine Coon queen with extensive mammary gland hyperplasia, a clinical examination, analyses of the progesterone (P4) concentrations and ultrasound examination were performed. Feline mammary fibroadenomatous hyperplasia associated with a high P4 concentration after spontaneous ovulation was confirmed. After 24 days of therapy with a progesterone antagonist, aglepristone, the symptoms of FMFH resolved. After the next eight weeks, the queen was mated after the owner's decision. In the third week of pregnancy, a relapse was detected (mammary gland enlargement, pain, discomfort). At the same time, no abnormalities in the uterus or embryos were detected via ultrasound. The P4 concentrations were under regular control. For the next two weeks, only conservative treatment with NSAIDs was used. The queen spontaneously delivered six kittens without any difficulties or perinatal complications 67 days after the first mating. The cat previously treated with aglepristone for FMFH was successfully bred, but FMFH symptoms returned when progesterone concentrations increased during pregnancy.